2015
DOI: 10.1021/acs.jpcb.5b00673
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Binary Mixture Systems of Saturated-Unsaturated Mixed-Acid Triacylglycerols: Effects of Glycerol Structures and Chain–Chain Interactions

Abstract: We systematically examined the phase behavior of binary mixtures of mixed-acid triacylglycerols (TAGs) containing palmitic and oleic acid moieties 1,3-dioleoyl-2-palmitoyl-glycerol (OPO), 1,2-dipalmitoyl-3-oleoyl-rac-glycerol (PPO), and 1,2-dioleoyl-3-palmitoyl-rac-glycerol (OOP), which are widely present in natural fats and are employed in the food, pharmaceutical, and cosmetic industries. Differential scanning calorimetry and X-ray diffraction methods were applied to observe the mixing behavior of PPO/OPO, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 36 publications
1
55
2
1
Order By: Relevance
“…In this study, we studied the crystallization of a binary mixture of 1,3-dioleoyl-2-palmitoyl-sn-glycerol (OPO) and 1,3-dipalmitoyl-2-oleoyl-sn-glycerol (POP) with an interest in using the two TAG for edible fats, having advantageous properties of no-trans, low-saturated, and high-oleic fats. Previous studies have shown that OPO and POP form molecular compound (MC) crystals at the ratio of OPO: POP = 1:1 mixture (Bayés-García, Calvet, Cuevas-Diarte, Ueno, & Sato, 2015;Ikeda, Ueno, Miyamoto, & Sato, 2010;Ikeda-Naito, Ogawa, & Ueno, 2017;Larsson, Quinn, Sato, & Tiberg, 2006;Minato et al, 1997;Moran, 1963;Sato & Ueno, 2014;Sibbald, Carney, & Marangoni, 2016). Its stable polymorphic form is β, which has a double-chainlength structure.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we studied the crystallization of a binary mixture of 1,3-dioleoyl-2-palmitoyl-sn-glycerol (OPO) and 1,3-dipalmitoyl-2-oleoyl-sn-glycerol (POP) with an interest in using the two TAG for edible fats, having advantageous properties of no-trans, low-saturated, and high-oleic fats. Previous studies have shown that OPO and POP form molecular compound (MC) crystals at the ratio of OPO: POP = 1:1 mixture (Bayés-García, Calvet, Cuevas-Diarte, Ueno, & Sato, 2015;Ikeda, Ueno, Miyamoto, & Sato, 2010;Ikeda-Naito, Ogawa, & Ueno, 2017;Larsson, Quinn, Sato, & Tiberg, 2006;Minato et al, 1997;Moran, 1963;Sato & Ueno, 2014;Sibbald, Carney, & Marangoni, 2016). Its stable polymorphic form is β, which has a double-chainlength structure.…”
Section: Introductionmentioning
confidence: 99%
“…Quite interestingly, the formation of MC crystals of POP/OPO and POP/PPO was confirmed in both neat liquid and in diluted n ‐dodecane solutions (Ikeda, Ueno, Miyamoto, & Sato, ; Ikeda‐Naito, Hondoh, Ueno, & Sato, ). Table indicates that the diversified mixing behavior of the major TAG is influenced by fatty acid moieties (chain length, saturated or unsaturated) and glycerol structures (chair or tuning fork) as thoroughly discussed by Bayes‐Garcia, Calvet, Cuevas‐Diarte, Ueno, and Sato (). The importance of the glycerol structures is clearly seen in POP/OOP (eutectic) and POP/OPO (MC forming), since the glycerol structures of POP and OPO are of tuning‐fork type, whereas OOP reveals chair‐type structure.…”
Section: Introductionmentioning
confidence: 93%
“…More experimental and modeling work is required to understand the mechanism. Binary phase behaviors of various saturated-unsaturated mixed-acid TAGs are summarized in Table 2 6, 9, 11 16,20,24,25,30 .…”
Section: Polymorphism and Mixing Behavior Of Enantiopure And Racemic mentioning
confidence: 99%
“…With a basic understanding of the MC formation mechanism, the phase behaviors of the binary mixtures of OPO, PPO, and OOP were recently examined systematically by Bayés-García et al 30 . It should be noted that OPO, PPO, and OOP are the counterpart TAGs of POP, OOP, and PPO, in which the positions of palmitic acid and oleic acid interchanged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation